The New World Gibbobruchus Pic (Coleoptera, Chrysomelidae, Bruchinae): description of a new species and phylogenetic insights into the evolution of host associations and biogeography - Manfio, Daiara; Jorge, Isaac R.; Morse, Geoffrey E.; Ribeiro-Costa, Cibele S. (Zootaxa, 2016)
The seed beetle Gibbobruchus tridentatus Manfio, Jorge & Ribeiro-Costa sp. nov. is described from the Amazon basin in Brazil (Acre) and Ecuador (Napo), and is included in an updated key to the species of Gibbobruchus Pic. This new species and the recently described G. bergamini Manfio & Ribeiro-Costa are incorporated into a phylogenetic reanalysis of the genus and into a comparative analysis of host plant use and biogeography. Species groups previously proposed were supported and the evolutionary history in host plant-use shows Gibbobruchus conserved at tribe level, Cercideae (Caesalpinioideae), with coordination between biogeographic expansion and host genus shifts. Both species, Gibbobruchus tridentatus Manfio, Jorge & Ribeiro-Costa sp. nov. and G. bergamini, were placed within the group scurra (G. tridentatus (G. scurra (G. cavillator+G. bolivianus+G. bergamini))) and supported by one synapomorphy. Additionally, we update geographic distributions and host plant records. Two hosts, Bauhinia argentinensis Burkart and B. tarapotensis Benth. are recorded for the first time as hosts for the genus and for the subfamily.